2011
DOI: 10.1021/ma2013173
|View full text |Cite
|
Sign up to set email alerts
|

Room Temperature Rapid Photoresponsive Azobenzene Side Chain Liquid Crystal Polymer

Abstract: A new room temperature photoresponsive side chain liquid crystalline polymer has been synthesized and tested. It combines a side-on azobenzene LC with a low glass transition temperature polysiloxane backbone to obtain a nematic LCP at room temperature. The LCP also exhibits a crystalline phase that is kinetically trapped by the nematic phase at room temperature. Thermal transitions were observed at −7, 42, and 73 °C for the T g, T m, and T iso, respectively, and polarizing optical microscopy with in situ UV ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 91 publications
0
34
0
Order By: Relevance
“…Previously, Petr et al observed a decrease in modulus as the cis state disrupted liquid crystalline order in a polymeric network. 25, 26 In addition, several studies have observed gel-sol transitions upon the disruption of hydrogen bonds between neighboring azobenzene units in supramolecular systems. 27, 28 Although the hydrogen bond structure in this system is still under investigation, the planar trans conformation may better be able to stabilize hydrogen bonds between the peptide crosslinkers, thereby rigidifying the substrate.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, Petr et al observed a decrease in modulus as the cis state disrupted liquid crystalline order in a polymeric network. 25, 26 In addition, several studies have observed gel-sol transitions upon the disruption of hydrogen bonds between neighboring azobenzene units in supramolecular systems. 27, 28 Although the hydrogen bond structure in this system is still under investigation, the planar trans conformation may better be able to stabilize hydrogen bonds between the peptide crosslinkers, thereby rigidifying the substrate.…”
Section: Resultsmentioning
confidence: 99%
“…Based on these characteristics, many potential applications can be proposed for this kind of organogel, such as so actuators, molecular switches and photomechanical systems. 12,[17][18][19][20] Experimental Materials 4-Aminophenol was obtained from Alfa Aesar Co., Inc. 4,4 0 -Biphenol, 2-(2-(2-chloroethoxy)ethoxy)ethanol, diethyl acetamidomalonate, potassium iodide (KI) and tetrabutyl orthotitanate (Ti(O i Pr) 4 ) were supplied by TCI Development Co., Ltd. Ethyleneglycol dimethyl ether was supplied by Aladdin Bio-Chem Technology Co., Ltd. Sodium nitrite (Na 2 NO 3 ), methanol (CH 3 OH), phenol, hydrochloric acid (HCl, 36%), potassium carbonate (K 2 CO 3 ), N,N-dimethylformamide (DMF), dichloromethane (CH 2 Cl 2 ), chloroform were (CHCl 3 ), tetrahydrofuran (THF) and dioxane were purchased from Sinopharm.…”
Section: Introductionmentioning
confidence: 99%
“…3(b)). The small attenuation length (∼100 nm), compared to that of liquid-crystal elastomer (∼1 μm), 31,32 is attributed mostly to high density of the azobenzene chromophores. 26 In fact, we experimentally confirmed the contraction of the Azo-1 nanowire at the surface region (<100 nm) upon UV irradiation, based on using a real-time grazing incidence X-ray diffraction (GIXD) method (Fig.…”
mentioning
confidence: 97%